Solar Charged Redox Flow Battery: A Tandem Photoelectrochemical Approach. Issue 5 (28th September 2018) - Durant, Brandon K.; She, Yuqi; Wang, Peng; Kraus, Theodore; Parkinson, Bruce A.
Abstract : A tandem two photoelectrode cell separated by a proton exchange membrane for simultaneous conversion of solar energy into both chemical and electrical energy was investigated by illumination of both a large bandgap photoanode, to produce a highly oxidized species, and a narrow bandgap photocathode, to produce a highly reduced species. The two photoelectrode configuration provides higher photovoltages than a single semiconducting material while also absorbing complementary portions of the solar spectrum leading to potentially higher energy conversion efficiencies. Utilization of kinetically fast redox couples overcomes the overpotential barriers required for water splitting as well as the difficulties associated with gas collection and transport. Additionally, the photopotentials obtained show that not only does this configuration not require external bias but excess electrical power could also be produced in addition to the storage of chemical energy. These experiments demonstrate the feasibility for highly efficient solar energy conversion by directly photocharging a redox flow battery.